First report of phoretic deutonymphs of Thyreophagus corticalis (Michael, 1885) (Acari: Acaridae) on Ixodes ricinus (Linnaeus, 1758) (Ixodida: Ixodidae) - Diana Rueda-Ramírez; Sara Weilage; Anna Obiegala; Lidia Chitimia-Dobler; Martin Pfeffer (Ticks and Tick-Borne Diseases)
Phoretic deutonymphs of Thyreophagus corticalis (Michael, 1885) were found associated with a male and nymphs of Ixodes ricinus during a sampling conducted in May 2024 in the district of Reutlingen, Baden-Württemberg, Germany, using the flagging method. A total of six deutonymphs were detected on four of the 652 ticks collected at four out of 25 sampling sites, indicating a geographically restricted and low incidence. This account is the first report of a phoretic association of T. corticalis with I. ricinus. We consider this phoretic association likely to be coincidental, possibly resulting from the ticks coming into contact with organic or decaying material at these four sampling sites where T. corticalis populations occurred.